Clostridium difficile infection in a French university hospital: Eight years of prospective surveillance study. Issue 23 (June 2016) - Khanafer, Nagham; Oltra, Luc; Hulin, Monique; Dauwalder, Olivier; Vandenesch, Francois; Vanhems, Philippe
Abstract : Abstract: The epidemiology of Clostridium difficile infection (CDI) has changed with an increase in incidence and severity. Prospective surveillance was therefore implemented in a French university hospital to monitor the characteristics of patients at risk and to recognize local trends. Between 2007 and 2014, all hospitalized patients (≥18 years) with CDI were included. During the survey, the mean incidence rate of CDI was 2.9 per 10, 000 hospital-days. In all, 590 patients were included. Most of the episodes were healthcare-associated (76.1%). The remaining cases were community-acquired (18.1%) and unknown (5.9%). The comparison with healthcare-associated cases showed that the community-acquired group had a lower rate of antimicrobial exposure ( P < 0.001), proton pump inhibitor ( P < 0.001), and immunosuppressive drugs ( P = 0.02). Over the study period, death occurred in 61 patients (10.3%), with 18 (29.5%) being related to CDI according to the physician in charge of the patient. Active surveillance of CDI is required to obtain an accurate picture of the real dimensions of CDI.